Neutropenic enterocolitis in a non-immunocompromised patient presenting with lower respiratory tract infection: a case report - Saha, Somesh; Roy, Aakash Guha; Sarkar, Shramana; Deb, Shramana; Mondal, Ritwick (International Journal of Research in Medical Sciences, 2022)
Neutropenic enterocolitis (NEC) has been widely reported in adults with myelofibrotic disorders, solid malignant tumors, bone marrow transplantation as well as in myelotoxic chemotherapy. Here we reported a case of a 66-year-old non-diabetic, hypertensive female without any prior history of immunosuppression or any underlying malignancy or related chemotherapy; who presented with severe dyspnoea, low grade fever and cough. Followed by a course of effective conservative management and initial stabilization, on investigation her TLC was found to be abnormally low with severe neutropenia and a hyperinflammatory response induced myelosuppression with LRTI was suspected. Subsequently, subcutaneous G-CSF, broad spectrum antibiotics were initiated along with supportive management. She developed abdominal distension, diffused pain and tenderness with hypoactive bowel on the following day. After 3 days of G-CSF trial, neutrophil count started to increase along with her overall improvement. CECT was performed with positive findings of multiple colonic short segment involvement without any stricture, pericolic fat stranding and perforation; reflecting towards a resolving neutropenic enteropathy.